Structure elucidation of a galactofuranose-rich heteropolysaccharide from aciduric fungus penicillium purpurogenum JS03-21 - Chen, Yin; Mao, Wenjun; Wang, Hui; Zhu, Weiming; Niu, Qingfeng; Fang, Xubo; Li, Tao (Glycoconjugate journal, 2015)
The exopolysaccharide-producing fungus Penicillium purpurogenum JS03-21 from the acidic purple clay was screened to develop greater insights into microbial exopolysaccharide resources from extremophilic microorganisms. An exopolysaccharide JS1-1 was purified from the fermented broth of the aciduric fungus using a combination of ethanol precipitation, anion-exchange and size-exclusion chromatography. JS1-1 was found to be a neutral heteropolysaccharide composed of galactose, mannose and glucose in the ratio of 7.9:2.1:1.0, with a molecular weight of about 26 kDa. JS1-1 was subjected to a series of methylation and partial acid hydrolysis reactions, as well as being analyzed by one- and two-dimensional nuclear magnetic resonance, and the results of these analyses revealed JS1-1 to be a galactofuranose-rich polysaccharide. The main chain of JS1-1 contained two regions, including a galactose part composed of a repeating trisaccharide unit [ i.e ., →5)-β-D-Gal f (1 → 5)-β-D-Gal f (1 → 6)-β-D-Gal f (1→], and a mannose section consisting of (1 → 6)-linked α-D-Man p residues. Two further segments [ i.e ., α-D-Glc p (1 → 2)-α-D-Gal f (1 → and α-D-Gal f (1 → 2)-α-D-Man p (1→] existed as branches that were linked to the O - 2 atoms of the (1 → 6)-β-D-Gal f and (1 → 6)-α-D-Man p regions of the main chain, respectively. The results of the current study demonstrate that JS1-1 is a unique polysaccharide that is rich in both α and β galactofuranose units and therefore different from most of the other known extracellular polysaccharides. The function of this polysaccharide is currently being researched in our laboratory.